Internet Individidual Use Of BRICS Countries In The 21st Centuries Per Mobile Cellular And Broadband Subscription - Hutabarat, Francis (Universitas Ibn Khladun Bogor, 2025)
This study looks on the effect of mobile cellular subscription and broadband subscription on internet individual use of BRICS countries in the 21st centuries. This research applies a quantitative approach by selecting BRICS countries, namely Brazil, Russia, India, China and South Africa as samples. Research information was obtained from 2000 to 2022 from the countries that are members of the BRICS. Samples were taken using a purposive sampling method, taking into account the appropriate size of 105 data for the research objectives. Data taken from the Our World in Data website and analyze using Eviews statistic software. From the results of the research that has been carried out, it can be concluded that Mobile cellular subscription has a significant influence on Internet Individual use in BRICS countries with the t-statistic found, 3.7860, 0.0003 probability. However, fixed broadband subscription sees different results. With this result, BRICS countries can value it and consider increasing the efficiency of mobile cellular subscriptions. Thus, the study suggests for BRICS countries to cultivate the benefit in economic growth, as people interacts with mobile phones and connectivity on the go, they who sees these opportunities will see mobile internet access facilitates the use of e-commerce platforms, mobile banking, and digital payment systems.